2012
DOI: 10.3389/fimmu.2012.00119
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Chemotaxis – Chemoattractants and Signaling Pathways

Abstract: Migration of mast cells is essential for their recruitment within target tissues where they play an important role in innate and adaptive immune responses. These processes rely on the ability of mast cells to recognize appropriate chemotactic stimuli and react to them by a chemotactic response. Another level of intercellular communication is attained by production of chemoattractants by activated mast cells, which results in accumulation of mast cells and other hematopoietic cells at the sites of inflammation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
154
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(160 citation statements)
references
References 215 publications
(259 reference statements)
4
154
2
Order By: Relevance
“…SCF promotes mast cell recruitment into various tissues and also promotes the maturation of mast cells. 26 Studies that involve bone marrow mast cells and peritoneal mast cells demonstrate a dependence on the SCF/c-Kit interaction for mast cell recruitment. 26 Our evaluation of the SCF/c-Kit interaction demonstrates that, in CCA cells, blocking the interaction between mast cells and CCA decreases CCA proliferation, angiogenesis, mast cell marker presence; EMT switch; and ECM breakdown, pinpointing this pathway as a potential therapeutic avenue for CCA treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCF promotes mast cell recruitment into various tissues and also promotes the maturation of mast cells. 26 Studies that involve bone marrow mast cells and peritoneal mast cells demonstrate a dependence on the SCF/c-Kit interaction for mast cell recruitment. 26 Our evaluation of the SCF/c-Kit interaction demonstrates that, in CCA cells, blocking the interaction between mast cells and CCA decreases CCA proliferation, angiogenesis, mast cell marker presence; EMT switch; and ECM breakdown, pinpointing this pathway as a potential therapeutic avenue for CCA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…26 Studies that involve bone marrow mast cells and peritoneal mast cells demonstrate a dependence on the SCF/c-Kit interaction for mast cell recruitment. 26 Our evaluation of the SCF/c-Kit interaction demonstrates that, in CCA cells, blocking the interaction between mast cells and CCA decreases CCA proliferation, angiogenesis, mast cell marker presence; EMT switch; and ECM breakdown, pinpointing this pathway as a potential therapeutic avenue for CCA treatment. In studies that involve metastatic nasopharyngeal carcinoma it was found that activation of SCF/c-Kit signaling potentially contributes to carcinogenesis and progression of this cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, the local concentration of S1P provides an important cue in the context of immunological function, lymphangiogenesis and blood vessel stabilization. Loss of S1PR1 in RBL-2H3 cells, derived from mast cells (a type of white blood cell), results in decreased chemotactic motility [29,30], and S1PR1 activation via S1P is required for lymphocyte egress from the thymus and secondary lymphoid organs in mice [28,31,32]. S1P promotes LEC sprouting in vitro in a manner that requires S1PR1 [33].…”
Section: Introductionmentioning
confidence: 99%
“…Inhalation of PGD 2 induced nasal blockage via the DP receptor in atopic rhinitis patients 9 . In addition, PGD 2 enhanced airway inflammation by accumulation of inflammatory cells via the DP receptor on epithelial cells 10,11 . Conversely, other studies have suggested anti-inflammatory roles for PGD 2 .…”
mentioning
confidence: 99%
“…Following the onset of inflammation, several chemoattractants are produced that stimulate the release of mast cell progenitors (MCps) from bone marrow (BM) into the circulation 2 . Circulating MCps migrate and mature peripherally in connective or mucosal tissues.…”
mentioning
confidence: 99%